Sport as a factor in the mental well-being of students with disabilities - Zakharova N.L. ,; Kotovskaya S.V. ,; Belenkova L.Yu. ,; Ostrovskiy A.N. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to identification of the peculiarities of mental states of students with disabilities involved in sports. Methods and structure of the study. The empirical approach to research was through experimentation. The data analysis was conducted using the IBM SPSS Statistics 27 statistical software and the Excel program. The study included students with disabilities who participated in sports and their peers, students from the 1st to 4th years of the Russian State University of Social Technologies. Results and conclusions. The disparities in the psychological states of students with disabilities who participate in sports and their peers were identified. Athletes are characterized by a predominance of positive emotions, which are closely linked to the manifestation of their volitional qualities and the ability to focus their attention. Student-athletes, on the other hand, experience negative emotional experiences during periods of inactivity, impulsive actions, and feelings of insecurity. These negative mental states are less likely to occur when mental processes are activated, physiological reactions change, or behavior is modified. The relationship between the mental states and personal characteristics of athletes with disabilities has been empirically demonstrated. The correlations that have been identified reveal the following patterns: as sensitivity to external stimuli and awareness of perception increases, so does the desire for independence; positive emotions enhance a sense of individuality; and as self-confidence grows, so does life satisfaction.; The experience of optimism enhances responsiveness and empathy. The feeling of joy is closely linked to perseverance and enthusiasm. As the number of actions increases, empathy, life satisfaction, and receptivity grow, while the desire to make a good impression diminishes.